IMPLEMENTASI PENDIDIKAN LIFE SKILL DALAM PEMBENTUKAN KEMANDIRIAN SANTRI - Desy Naelasari (DAR EL-ILMI : Jurnal Studi Keagamaan, Pendidikan dan Humaniora, 2018)
Learning in school should be useful for the provision of student life in the present and the future. Boarding school program the students are generally preoccupied with the Koran. This is in contrast with the PP-UW, students are not only taught here mrngaji, but students are also equipped with the skills / life skills / commonly called pious charity. Through this pious charity, the students had a spirit of independence. This study was to determine how the Life Skill education at UW-PP, PP-independence students at UW and implementation of Life Skill Education in the Formation of Self-Reliance Students in PP-UW. This research included the category of field research (fieldwork). Dippergunakan data collection techniques; interviews, observations and the data dokumentasi.analisis include; reduction, presentation and conclusion and verification. While the validity of test data is done by triangulai techniques and resources. From this research, life skill education in PP-UW existed since Abah Qoyim leadership. Education at boarding school al Urwatul Wutsqo is tarekah education where each job prioritizing practice than theory. Autonomy of each students in PP-UW, can be demonstrated by the students responsibility for their respective duties, students proficient create on, students become spoiled, students can determine the direction of his own life, the students were able to adapt to the outside environment, students become dependent on others , students skilled in solving their own problems, and students can take care of himself. Self-reliance here is not simply to open a business, but to glorify God. Implementation of life skills education in the formation of self-sufficiency in PP-UW students can be seen from their charitable activities in PP-UW pious soul kemandiran establish yourself each students. So, when the students out of the hut, they have the skill / expertise, skills in other areas, which will be useful in future society.